Study on the C-E Translation of Government Work Reports from 2019 to 2023 from the Perspective of Eco-Translatology - Kang, Fei (Transactions on Social Science, Education and Humanities Research, 2024)
Eco-translatology is a translation theory integrated with ecology. Publicity translation has a vital impact on making Chinese voices go global. Taking the C-E translation of Government Work Reports from 2019 to 2023 as an example, this paper analyzes their translation methods from the perspective of "three-dimensional" transformation, including linguistic dimension, cultural dimension and communicative dimension. At present, eco-translatology seldom focuses on the translation of publicity texts. According to the "three-dimensional" transformation, this paper aims to explore the translation rules of publicity texts with Government Work Reports as an example from the perspective of eco-translatology. Guided by eco-translatology, the translation of Government Work Reports can be further developed in the future.